Household expenditure of smokers and ex-smokers across socioeconomic groups: results from a large nationwide Australian longitudinal survey - Anita Lal; Mohammadreza Mohebi; Sarah L. White; Michelle Scollo; Nikki McCaffrey (BMC, 2022)
Abstract Background Countries with best practice tobacco control measures have experienced significant reductions in smoking prevalence, but socioeconomic inequalities remain. Spending on tobacco products, particularly by low-income groups can negatively affect expenditure on other goods and services. This study aims to compare the household expenditure of adults who smoke tobacco products and those who formerly smoked across socioeconomic groups. Methods Daily smokers and ex-smokers were compared using the Household, Income and Labour Dynamics in Australia Survey, over 7 waves. Adults who never smoked were not included. Participants were continuing sample members across waves. Mean number of participants per wave was 2505, 25% were smokers and 75% ex-smokers. The expenditure variables investigated included tobacco products, alcohol, motor vehicle fuel, health practitioners, insurance, education, and meals eaten out. Regression models using the generalized estimating equation technique were employed to compare expenditure data aggregated across the waves by Socioeconomic Index for Areas (SEIFA) quintiles of relative socio-economic advantage/disadvantage while accounting for within-participant autocorrelation. Quintiles are ranked by information such as the income, occupation and access to material and social resources of the residents. Results Smokers from all quintiles spent significantly less per year on meals out, education and insurance than ex-smokers (p < 0.001). Smokers from quintiles 2-5 spent less on groceries, medicines, and health practitioners (p < 0.01). Smokers from quintiles 1 and 2 (most disadvantaged), spent less on motor vehicle fuel than ex-smokers ($280;95%CI: $126-$434), ($213;95%CI: $82-$344). Smokers from quintiles 2 and 3 spent more on alcohol ($212;95%CI: $86-$339), ($231.8;95%CI: $94-$370) than ex-smokers. Smokers from the least disadvantaged groups spent less on clothing than ex-smokers ($348;95%CI: $476-$221), ($501; 95%CI: $743-$258). Across the whole sample, smokers spent more than ex-smokers on alcohol ($230;95%CI:$95-$365) and less on meals out ($361;95%CI:$216-$379), groceries ($529;95%CI:$277-$781), education ($456;95%CI:$288-$624), medicine ($71;95%CI:$38-$104), health practitioners ($345;95%CI:$245-$444) and insurance ($318;95%CI:$229-$407). Conclusions Smoking cessation leads to reallocation of spending across all socioeconomic groups, which could have positive impacts on households and their local communities. Less spending on alcohol by ex-smokers across the whole sample could indicate a joint health improvement associated with smoking cessation.